THE IMPORTANCE OF HARMONY OF SECULAR AND RELIGIOUS KNOWLEDGE IN THE SPIRITUAL DEVELOPMENT OF HUMAN (American Journal of Research in Humanities and Social Sciences, 2024)
Everyone has material as well as spiritual needs. Both of them play an incomparable role in the development of humanity. One of our spiritual needs is religion. From the results of scientific works on religion it is clear that religiosity is a common quality of all humanity, both ancients and moderns are equal in it. These processes manifested and developed in their own way in each era. Research and reforms carried out in the new Uzbekistan are aimed at ensuring a commonality of both religious and secular knowledge and values. The main goal is to give young people religious knowledge using scientifically proven sources, to form religious values in them, and to prevent them from falling into various alien ideas and wandering trends. Also, the practical method used in preparing the article, that is, the results of an open structured anonymous survey, will help teachers of “Religious studies” determine what other aspects of the subject they should pay attention to during the lesson, knowing what problems and questions interest young people helps them to prepare thoroughly. After all, the question of religion is not only interesting, but also a very delicate issue.